Exploration of Natural Chemical Compounds as Novel Post-Pandemic Antiviral Agents: A Review - Anggraini, Welly (Jurnal Pijar Mipa, 2025)
The COVID-19 pandemic has accelerated the search for effective, safe, and sustainable antiviral agents. One promising approach is the utilization of natural chemical compounds derived from plants, microorganisms, and marine organisms. These compounds, such as flavonoids, alkaloids, terpenoids, and polyphenols, have long been known for their broad biological activities, including antiviral properties. This article aims to explore the potential of natural chemical compounds as new post-pandemic antiviral candidates through a systematic literature review of 28 scientific articles published between 2019 and 2024 from major databases such as PubMed, ScienceDirect, and SpringerLink. The findings indicate that 24 out of 28 reviewed compounds demonstrated significant antiviral activity, with 15 flavonoids targeting viral protease or spike protein through mechanisms like Mpro inhibition, ACE2 interaction, or cytokine modulation. Key challenges include low bioavailability, complexity in compound isolation, and lack of pharmaceutical standardization. However, advanced technological approaches such as nanoformulation, semi-synthetic analogue development, and the use of bio-refinery systems offer potential solutions to enhance the stability and effectiveness of these compounds. This article also highlights the importance of policy support and interdisciplinary collaboration in accelerating the translation of natural compounds from laboratory research to clinical application. The review offers practical implications for pharmaceutical innovation, particularly in biodiversity-rich countries such as Indonesia.